If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -1y) + 6y = 0 (2x * 3 + -1y * 3) + 6y = 0 (6x + -3y) + 6y = 0 Combine like terms: -3y + 6y = 3y 6x + 3y = 0 Solving 6x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 6x + 3y + -3y = 0 + -3y Combine like terms: 3y + -3y = 0 6x + 0 = 0 + -3y 6x = 0 + -3y Remove the zero: 6x = -3y Divide each side by '6'. x = -0.5y Simplifying x = -0.5y
| 0.3(y+4)=0.4(y-2) | | 19=35+9x | | 2(-1)-4-y=12 | | 3y-(y+2x)+x= | | 6y-9-3y+8=0 | | 2(0)-4-y=12 | | 4y-5x=4 | | 2(1)-4-y=12 | | 2z-18-4z=-9 | | -7+u=3 | | y-53=294 | | X^2+6x+6.75=0 | | 4x+7x-3=0 | | -101=w+5.3 | | -0.8k-3.1=.5 | | 4(2x-1)-(3-1)=3 | | 9x^2+18x=22 | | 4(2x-1)-(3x-1)=3 | | x+2/4=27/12 | | F(x)=x*2-6x-15 | | 31=7c+-74 | | 15*15+9*9=x*x | | 4x+206=12+10 | | x-8+9-3=11 | | 6x-5-4x=17 | | Sin(x)=0.75 | | x=A+y+1 | | x-0.8=2.9 | | (12-x)+(x-14)=11 | | a=b-3x | | 0.125x+0.25(1500+x)=195 | | -7x+17y=-13 |